2011
DOI: 10.1016/j.surfcoat.2011.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Powder stream characteristics in cold spray nozzles

Abstract: Abstract. The exponential increase of industrial demand in the past two decades has led scientists to the development of alternative technologies for the fast manufacturing of engineering components, aside from standard and time consuming techniques such as casting or forging.Cold Spray (CS) is a newly developed manufacturing technique, based upon the deposition of metal powder on a substrate due to high energy particles impacts. In this process, the powder is accelerated up to considerable speed in a convergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(25 citation statements)
references
References 19 publications
0
21
0
4
Order By: Relevance
“…Razvijeno je mnogo različitih postupaka nanošenja prevlaka, a jednu veliku grupu čine postupci metalizacije. Hladna metalizacija (Cold Spaying) je postupak metalizacije koji se konstantno razvija i predstavlja jedan od postupaka budućnosti [3]. U poslednjih nekoliko godina, zbog velike potražnje za proizvodnjom metalnih prevlaka u različitim industrijskim postrojenjima, postupci metalizacije i njihove tehnologije evoluirali su od začetaka (gasnoplamena metalizacija, elektrolučna metalizacija žicom itd.…”
Section: Uvodunclassified
See 1 more Smart Citation
“…Razvijeno je mnogo različitih postupaka nanošenja prevlaka, a jednu veliku grupu čine postupci metalizacije. Hladna metalizacija (Cold Spaying) je postupak metalizacije koji se konstantno razvija i predstavlja jedan od postupaka budućnosti [3]. U poslednjih nekoliko godina, zbog velike potražnje za proizvodnjom metalnih prevlaka u različitim industrijskim postrojenjima, postupci metalizacije i njihove tehnologije evoluirali su od začetaka (gasnoplamena metalizacija, elektrolučna metalizacija žicom itd.…”
Section: Uvodunclassified
“…Kod tradicionalnih postupaka metalizacije dodatni materijal je zagrejan do visokih temperatura, pa prevlake mogu da sadrže visok procentualni udeo oksida, što ograničava dalju širu upotrebu ovih postupaka. Ova ograničenja moguće je prevazići pomoću postupka hladne metalizacije, koji je razvijen relativno skoro [3][4][5]. Hladna metalizacija (Cold Spraying) u literaturi se može naći i pod drugim nizivima kao npr.…”
Section: Uvodunclassified
“…It is worth noting that all particles are assumed to be injected in X direction. Actually, the particles have a random injection direction at the Pressure Outlet1 [14,15]. As in conventional nozzle, most of the particles always travel through the highest gas velocity area in the nozzle.…”
Section: Acceleration Behavior Of Particle In the Nozzlementioning
confidence: 99%
“…Studying of relevant literature has shown that CGDS provides the deposition dynamics that could not be achieved literally by conventional spraying techniques such as plasma spray, wire arc, high-velocity oxy-fuel (HVOF) and wire flame which associate with phase properties changes and high temperatures. These associated limitations can easily be overcome by newly developed technology namely cold spraying coating technology [1,[11][12][13]. Cold spraying processes offers several advantages both in the processing itself and in the deposition result.…”
Section: Introductionmentioning
confidence: 99%